IN VITRO ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF HIGH ALTITUDE MEDICINAL PLANT TANACETUM GRACILE - MANISHA BHATNAGAR; ANUPAMA SHARMA AVASTHI; SABARI GHOSAL (International Journal of Pharma and Bio Sciences, 2017)
As a part of our ongoing investigation on high altitude medicinal plants, we investigated Tanacetum gracile (Asteraceae) by bioassay guided fractionation for antibacterial and antioxidant activity. The methanolic extract of the plant was fractionated into n-hexane (n-Hex), dichloromethane (DCM), ethylacetate (EtOAc) and aqueous fractions. The antibacterial activity of the fractions was evaluated against three Gram negative viz., Escherichia coli, Acinetobacter sp. and Serratia sp., and two Gram positive including Staphylococcus aureus and Enterococcus sp. MDR clinical isolates. As, oxidative stress is a major cause of cognitive, cardiovascular diseases and cancer, and plant is the main source of antioxidant compounds, we evaluated the antioxidant potential of the fractions by chemical assays including total phenolic and flavonoid content, DPPH scavenging potential and FRAP assays. The results showed that EtOAc fraction possesses significant antibacterial activity against Serratia sp. and also commendable antioxidant activity (DPPH IC50 37.38 ± 0.4 μg/mL) comparable to that of vitamin C. Phytochemical screening of the fractions revealed the presence of phenolics including flavonoids in the fraction. The results may offer the use of the plant fraction as herbal remedy in the therapy of pathological conditions related to multi drug resistant microbes and generation of free radicals. Further phytochemical analysis in this regard could lead to some new drug candidates.